Efforts to Improve Students' Logical Thinking Skills by Applying the Problem-Based Learning Model to Mathematics Learning at MIN Payaseunara - Rosdiah; Helvia Riany (MANDAILING GLOBAL EDUKASIA, 2025)
This classroom action research aimed to improve students’ logical thinking skills in mathematics learning through the implementation of the Problem-Based Learning (PBL) model at MIN Payaseunara. The study was conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 28 fifth-grade students. Data were collected using logical thinking skill tests, observation sheets of teacher and student activities, and field notes. The indicators of logical thinking measured included reasoning ability, problem analysis, systematic solution planning, and conclusion drawing. The findings showed a significant improvement in students’ logical thinking skills after the implementation of PBL. In the pre-cycle stage, the average score of students’ logical thinking ability was 59.21, with only 39.29% of students achieving the minimum mastery criterion. After the implementation of PBL in Cycle I, the average score increased to 70.46 and learning mastery improved to 67.86%. Furthermore, Cycle II demonstrated a more substantial improvement, with the average score reaching 82.14 and mastery learning increasing to 89.29%. Observation results also indicated that teacher activity improved from 72.50% in Cycle I to 90.00% in Cycle II, while student learning activity increased from 68.75% to 88.50%. These results confirm that the PBL model effectively enhances students’ logical thinking skills by encouraging active engagement, collaborative problem-solving, and structured reasoning processes. Therefore, Problem-Based Learning can be recommended as an effective instructional strategy to improve logical thinking competence in elementary mathematics education.